2020
DOI: 10.2196/13388
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Gamblers Who Use the French National Problem Gambling Helpline and Real-Time Chat Facility: Longitudinal Observational Study

Abstract: Background Problem gambling is a growing public health issue that is characterized by low rates of face-to-face help seeking. Helplines and real-time chat services could reduce shortfalls in treatment. Objective This study aimed to (1) describe the characteristics of gamblers contacting a government-funded help service, (2) study the evolution of their characteristics over time, (3) evaluate the differences between subgroups (ie, gender, media used for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Sample characteristics that may act as moderators in the relationship between gambling problems and suicidality include sex, age, and psychiatric comorbidity. Consistent with suicidology research in general, several studies among individuals with gambling problems have reported higher prevalence rates of suicidal ideation and suicide attempts among women compared to men (e.g., Carr et al, 2018; Pavarin et al, 2022; Ronzitti et al, 2017), albeit not consistently (e.g., Darbeda et al, 2020; Weinstock et al, 2014). Other studies have reported age to be an influential factor, where some studies have found younger age to be associated with increased risk for suicidality among individuals with gambling problems (Karlsson & Håkansson, 2018; Kausch, 2004; Leung & Tsang, 2011).…”
Section: Gambling Problemssupporting
confidence: 63%
See 1 more Smart Citation
“…Sample characteristics that may act as moderators in the relationship between gambling problems and suicidality include sex, age, and psychiatric comorbidity. Consistent with suicidology research in general, several studies among individuals with gambling problems have reported higher prevalence rates of suicidal ideation and suicide attempts among women compared to men (e.g., Carr et al, 2018; Pavarin et al, 2022; Ronzitti et al, 2017), albeit not consistently (e.g., Darbeda et al, 2020; Weinstock et al, 2014). Other studies have reported age to be an influential factor, where some studies have found younger age to be associated with increased risk for suicidality among individuals with gambling problems (Karlsson & Håkansson, 2018; Kausch, 2004; Leung & Tsang, 2011).…”
Section: Gambling Problemssupporting
confidence: 63%
“…Additionally, two studies (Cunningham-Williams et al, 2007; Schwarz & Lindner, 1992) were based on (cross-sectional) data collected in experimental studies (i.e., clinical interventions). Moreover, 11 studies (Chaput et al, 2007; Darbeda et al, 2020; Feigelman et al, 2006; Jeannot et al, 2023; Jolly et al, 2021; Karlsson & Håkansson, 2018; Ledgerwood et al, 2013; Morefield et al, 2014; Pavarin et al, 2021, 2022; Slutske et al, 2022) employed longitudinal designs, including four studies (Karlsson & Håkansson, 2018; Pavarin et al, 2021, 2022; Slutske et al, 2022) that employed a longitudinal cohort study design. Yet, only one of the longitudinal studies (i.e., Slutske et al, 2022) provided longitudinal associations on the relationship between gambling problems and suicidality.…”
Section: Resultsmentioning
confidence: 99%
“…In other reporting, approximately 40 percent of help-seekers have been identified as presenting a risk of suicide (17). In community samples, between 17 and 39 percent of those who gamble problematically have been reported to have suicide ideation and between 2 and 57 percent have reported suicide attempts (18)(19)(20)(21)(22). Suicidality also appears to increase alongside the severity of gamblingrelated problems (11,14,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, help line services have witnessed a significant increase in the volume of suicide-related presentations resulting from the COVID-19 pandemic [ 12 , 13 ]. Help line services support important avenues of suicide detection and prevention by providing equitability of access, promotion of disclosures and trust, and supplementation of traditional forms of health care [ 14 ]. However, suicide assessment via telehealth is challenged by the absence of nonverbal cues, by time limitations, and by the reticence of some callers to verbally express suicidal intent [ 15 ].…”
Section: Introductionmentioning
confidence: 99%